PENGARUH TOTAL ASSETS TURNOVER (TATO), NET PROFIT MARGIN (NPM) DAN DEBT TO EQUITY RATIO (DER) TERHADAP PERUBAHAN LABA DI PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN TAHUN 2012-2017 - Nababan, Suryani; Nainggolan, Eva Roma; Tobing, Debi; Sembiring, Samuel Abel Tanta; Luck Amelia S, Jholant Bringg (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Abstract This study aims to determine whether Total Assets Turnover (TATO), Net Profit Margin (NPM) and Debt to Equity Ratio (DER) to Profit Changes at PT. Nusantara III Plantation (Persero) Medan in 2012-2017. The results showed that the value of Fcount> Ftable was 16,542> 2.74 with a significant value of Î± (0,000 <0,05) and the value of tcount and ttable of each variable namely tcount> Total Assets Turnover (TATO) -2,364> 1 , 99547, Î± (0.021 <0.05). Net Profit Margin (NPM) 6,425> 1,99547, Î± (0,000 <0,05). Debt to Equity Ratio (DER) -1.109 <1.99547, Î± (0.271> 0.05). The conclusions in this study that simultaneously Total Assets Turnover (TATO), Net Profit Margin (NPM) and Debt to Equity Ratio (DER) affect the Profit Changes at PT. Perkebunan Nusantara III (Persero) Medan, and partially Total Assets Turnover (TATO) has a significant negative effect, Net Profit Margin (NPM) has an influence on Profit Changes Debt to Equity Ratio (DER) does not have at PT. Nusantara III Plantation (Persero) Medan in 2012-2017.